Long-term survival in pseudo-Meigs' syndrome caused by ovarian metastases from colon cancer. Issue 1 (December 2016) - Tajima, Yosuke; Kameyama, Hitoshi; Yamada, Saki; Yagi, Ryoma; Nakano, Masato; Nagahashi, Masayuki; Shimada, Yoshifumi; Sakata, Jun; Kobayashi, Takashi; Umezu, Hajime; Wakai, Toshifumi
Abstract Background Meigs' syndrome is defined as the co-existence of benign ovarian fibroma or fibroma-like tumor, ascites, and pleural effusion. In contrast, pseudo-Meigs' syndrome is defined as the co-existence of other ovarian or pelvic tumors, ascites, and pleural effusion. In Meigs' and pseudo-Meigs' syndromes, ascites and pleural effusion resolve promptly after the complete resection of the ovarian or pelvic tumor(s). Secondary ovarian tumors from colorectal gastrointestinal metastases rarely cause pseudo-Meigs' syndrome; only 11 cases of pseudo-Meigs' syndrome secondary to colorectal cancers have been reported in the literature. Therefore, the prognosis and etiology of pseudo-Meigs' syndrome caused by ovarian metastasis from colorectal cancers remain unclear. Case presentation We report here a rare case of pseudo-Meigs' syndrome caused by ovarian metastases from sigmoid colon cancer with long-term survival. A 47-year-old woman presented with abdominal distention of 1-month duration. She developed acute dyspnea 2 weeks after the initial presentation. Colonoscopy and computed tomography revealed sigmoid colon cancer with an ovarian metastasis, along with massive ascites and bilateral pleural effusion. Emergency operation, including bilateral oophorectomy and sigmoidectomy, was performed. Subsequently, ascites and bilateral pleural effusion resolved rapidly. Curative hepatic resection was performed for liver metastases 29 months after the first operation, and as of this writing, the patient is alive with no evidence of a disease 78 months after the first operation. In general, colorectal cancer with ovarian metastasis is hard to cure, and long-term survival in patients with colorectal cancer with pseudo-Meigs' syndrome is rare. Our experience suggests that curative resection for pseudo-Meigs' syndrome caused by ovarian metastasis from colorectal cancer may offer long-term survival. Conclusions Our experience suggests that pseudo-Meigs' syndrome can occur in a patient with colorectal cancer after metastasis to the ovaries, causing massive ascites and pleural effusion. Aggressive treatment, including R0 resection, for this disease if allowed by the patient's general condition may offer long-term survival.